Crime, Fear, and Control in Neighborhood Commercial Centers: Minneapolis and St. Paul, 1970-1982 - McPherson, Marlys ([Verlag nicht ermittelbar], 1987)
The major objective of this study was to examine how physical characteristics of commercial centers and demographic characteristics of residential areas contribute to crime and how these characteristics affect reactions to crime in mixed commercial-residential settings. Information on physical characteristics includes type of business, store hours, arrangement of buildings, and defensive modifications in the area. Demographic variables cover racial composition, average household size and income, and percent change of occupancy. The crime data describe six types of crime: robbery, burglary, assault, rape, personal theft, and shoplifting.